Active Citizens and Retirement Planning: Enlarging Freedom of Choice in the Course of Pension Reforms in Nordic Countries and Germany - Karl Hinrichs (Universität Bremen, Zentrum für Sozialpolitik (ZeS), 2004)
One feature of recent pension reforms in OECD countries has been that more individual responsibility is transferred to employees and in particular to those approaching the end of their working life. Enlarged freedom of choice concerns the timing of retirement with corresponding consequences for the level of public pensions as well as the participation in supplementary pension schemes and subsequent decisions about investment of savings, take out of benefits etc. Within such changed framework individual retirement planning becomes more complex and risky. Starting from the question why the government is in the "pension business" at all, the paper explores the reasons (and the extent) of enlarging freedom of choice in four countries where major pension reforms have recently taken place (Finland, Germany, Sweden) or are entering the agenda (Norway). The risks of increased self-responsibility with regard to provision for old age are analyzed in general, and the concrete policy changes are evaluated comparatively in view of respective institutional legacies and current challenges and conflicts.
Keywords: 330; Rentenreform; Alterssicherung; Ältere Arbeitskräfte; Verantwortung; Vergleich; Finnland; Deutschland; Schweden; Norwegen